The eloquence of the image in the poetry of Al_Kansaa (a reading in the poetics analogy) - تيسير جريكوس; محمد مسعود; ديما محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Al_ Kansaa is a prominent poet who excelled in saying poetry with its various purposes, and her name was associated with lamentation in particular, as she gave him a special place in her poetry, this was because of the misfortunes that she faced in her life, and because of the death that her loved ones were absent from, and her poetry was a sad influential and effective melody with his eloquence, images, the quality of her speech and his sobriety, this is the speech through which she showed her emotions using the analogy of its different types, in the tight construction of the elements of her images, and this is what leads to creativity and excellence.